Joule heating of solid state lighting - Yee, Kar Yin. (2009)
This project involved the finite element modeling on joule heating of Solid State Lighting (SSL). In this project, a specific failure mechanism-Joule heating that degrades the lifespan of SSL was targeted. Joule heating had reduced both the optical efficiency and lifespan of SSL. As a certain amount of current was passed through the diode, part of the input power will be dissipated as heat. This prevents 100% power conversion into optical which means a reduction in efficiency.